Estrategias de RSE en las PYMES del sector manufacturero de la ciudad de Santiago de Cali - Valle del Cauca (2020)
The importance and fundamental role played by micro-enterprises in the economic and social sphere of Colombia is remarkable. Currently there are 1,200,000 micro-enterprises, which generate around 2.8 million jobs, and which also contribute about 20 percent. percent of total production of goods and services or annual Gross Domestic Product (GDP) in Colombia. However, it is a sector lacking state support. It is essential to understand that CSR is about both internal and external behavior of the organization, which seeks to generate mutual benefits between it and the community, and for which a fluid and open relationship between all members of the environment is necessary. Corporate social responsibility went from being philanthropy or myth to becoming a prevailing reality in each of the activities carried out by companies and their different interest groups, thus adopting greater strength and interest in the social concept. It was found that the managers of micro-enterprises in the leather and leather goods sector in the city of Santiago de Cali interpret CSR as the responsibility to be assumed with respect to stakeholders, but in practice it is different, since each one of the activities carried out in this regard are totally empirical and focused only internally, thus neglecting to meet the expectations of other stakeholders. It is also established that there is ignorance about the subject and although it is recognized that CSR contributes to the competitiveness of micro-enterprises in the sector and significant efforts are made in this regard, it is not part of the organization's strategic plan. This monograph aims to identify the different CSR strategies in the footwear, leather and leather goods sector of SMEs in the city of Cali as a commitment to a sustainable business model and the reader will find that three objectives are proposed as follows The first one dedicated to characterizing CSR strategies as a competitiveness factor for SMEs in the footwear, leather and leather goods sector in Santiago de Cali under the ISO 26000 standard The second, to know if there is integration of social responsibility within the policies and action strategies of SMEs in the footwear, leather and leather goods sector in the city of Santiago de Cali under the ISO 26000 standard. The third, Determine the impact on the business plan of SMEs in the footwear, leather and leather goods sector that implement CSR strategies